2019
DOI: 10.22317/jcms.v5i3.609
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of breast cancer among Iraqi women

Abstract: Objectives: This study aimed to identify the risk factors of Breast Cancer among Iraqi women. Methods: A retrospective case control study, done on 147 breast cancer cases compared with 161 non- malignant cases selected randomly from women health center in Al-Elwyia maternity teaching hospital. Results: increased risk for breast cancer significantly associated with increased age especially ≥ 60 years, widow or divorced women(OR 3.7, CI (1.5-8.5)), menopause ((OR 6.43, CI(3.58-11.9)),age at menarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…This result aligns with other studies (47,48) but is unlike a study conducted by S.K. Abedalrahman et al (49), where menstrual irregularity was associated with an increased risk of BC.…”
Section: Jsmc 469supporting
confidence: 92%
“…This result aligns with other studies (47,48) but is unlike a study conducted by S.K. Abedalrahman et al (49), where menstrual irregularity was associated with an increased risk of BC.…”
Section: Jsmc 469supporting
confidence: 92%
“…The study found that among the women who participated, percent had a personal history of breast cancer, 6.66 percent had a personal history of breast cancer, 8.30 percent were 168 centimeters or taller, 2.42 percent had a benign breast disease, 0.80 percent had their first menstrual period at age 11 or younger, 6.66 percent had received radiotherapy to the chest area, and the women who participated had low levels of unchangeable risk factors. While there was no significant difference between the groups in terms of family history of breast cancer or age at menopause in a case-control study of healthy women and women with breast cancer in Iraq (Abedalrahman et al, 2019), there was a significant difference found regarding age at menarche. Eighty-one percent of the 1172 women with breast cancer in Iraq in a retrospective research reported no history of breast cancer in their families (Alwan et al, 2019).…”
Section: Resultsmentioning
confidence: 73%
“…In this country, prior literature indicates that breast cancer is diagnosed at advanced stages, which leads to a high proportion of women requiring radical mastectomy; they are then offered breast reconstruction surgery (BRS) [ 7 ]. The younger population in Iraq, as in many other middle-income countries, means that women with breast cancer who face mastectomy and BRS are much younger than those in Europe [ 8 ]. Breast reconstruction (BR) in Iraq occurs but to a lesser extent than neighbouring countries, with much emphasis put on the aesthetic value of this surgery, where some women opt for this surgery to enhance their looks.…”
Section: Introductionmentioning
confidence: 99%